2017
DOI: 10.2147/cmar.s147326
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint blockade in solid tumors and B-cell malignancies, with special consideration of the role of CD200

Abstract: In the ontogeny of a normal immune response, a series of checkpoints must be overcome to ensure that unwanted and/or harmful self-directed activation responses are avoided. Many of the molecules now known to be active in this overseeing of the evolving immune activation cascade, contributing inhibitory signals to dampen an overexuberant response, belong to the immunoglobulin supergene family. These include members of the CD28/CTLA-4:B7.1/B7.2 receptor/ligand family, PD-1 and PDL-1, CD200 and CD200R, and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Moreover, the findings in the current study demonstrated that CD200 positive expression was an independent predictor of MDS transformation to acute myeloid leukemia. These findings were in parallel with that reported in the previous studies which confirmed the prognostic relevance of high CD200 expression in MDS patients (Tiribelli et al, 2017;Gorczynski et al .,2017;Coles et al ., 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the findings in the current study demonstrated that CD200 positive expression was an independent predictor of MDS transformation to acute myeloid leukemia. These findings were in parallel with that reported in the previous studies which confirmed the prognostic relevance of high CD200 expression in MDS patients (Tiribelli et al, 2017;Gorczynski et al .,2017;Coles et al ., 2012).…”
Section: Discussionsupporting
confidence: 92%
“…These genes include the immune and tumor suppressor genes, ADAM23 [27] and BACH2 [28] and CD200, a molecule that helps to regulate immune activation. [29] All three of these genes were downregulated in the A-T subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of CD200R is restricted predominantly to cells of macrophage and myeloid lineage. CD200-CD200R pathway in the context of tumors has been most extensively studied in hematologic malignancies such as mature B-cell neoplasms, CLL and AML 33 . In solid tumors, CD200 expression has been demonstrated on ovarian cancer, melanoma, neuroblastoma and renal cancer cell lines 34 .…”
Section: Discussionmentioning
confidence: 99%